Student nurses’ experiences of undignified caring in perioperative practice – Part II - Willassen, Elin (Nursing ethics, 2015)
Background:In recent years, operating theatre nurse students’ education focused on ethics, basic values and protecting and promoting the patients' dignity in perioperative practice. Health professionals are frequently confronted with ethical issues that can impact on patient’s care during surgery.Objective:The objective of this study was to present what operating theatre nursing students perceived and interpreted as undignified caring in perioperative practice.Research design:The study has a descriptive design with a hermeneutic approach. Data were collected using Flanagan’s critical incident technique.Participants and research context:Operating theatre nurse students from Sweden and Norway participated and collected data in 2011, after education in ethics and dignity. Data consisting of 47 written stories and the text were analysed with hermeneutical text interpretation.Ethical considerations:The study was approved by the Karlstad University's Research Ethics Committee.Findings:The findings show careless behaviour and humiliating actions among health professionals. Health professionals commit careless acts by rendering the patient invisible, ignoring the patient’s worry and pain and treating the patient as an object. They also humiliate the patient when speaking in negative terms about the patient’s body, and certain health professionals blame the patients for the situation they are in. Health professionals lack the willingness and courage to protect the patient’s dignity in perioperative practice.Discussion:In the discussion, we have illuminated how professional ethics may be threatened by more pragmatic and utilitarian arguments contained in regulations and transplant act.Conclusion:The findings reveal that patients were exposed to unnecessary suffering; furthermore, the operating theatre nurse students suffered an inner ethical conflict due to the undignified caring situations they had witnessed.